Hubungan Perilaku Picky Eating dan Status Gizi dengan Kemampuan Short Term Memory pada Anak Usia Prasekolah - Madu, Yunita Gabriela; Sambo, Mery; Ganut, Felisima; Saranga, Jenita Laurensia; Rahmawati, Agustini Liviana Dwi; Padang, Alfrida Dua (Universitas Hang Tuah Pekanbaru, 2025)
Preschool children often exhibit picky eating, choosing only foods they like, leading to stunted growth and development. In addition to growth problems, nutrition can also affect cognitive development, namely, short-term memory skills. The purpose of the study was to determine the relationship between picky eating behavior and nutritional status, as related to short-term memory ability, in preschool-age children in the Working Area of the Pannambungan Health Center, Makassar City. This type of research uses a descriptive analysis approach with a cross-sectional design with independent variables of picky eating behavior, nutritional status, and dependent variables, namely short-term memory ability measured at one time, with a total of 76 respondents who have preschool-age children, taken by purposive sampling technique, and data analyzed using the chi-square test. The results of the study yielded a p-value of p < α (p = 0.000), indicating a relationship among picky eating, nutritional status, and short-term memory ability in preschool-age children. The conclusion in this study is that picky eating behavior and nutritional status affect short-term memory ability in preschool-age children. Therefore, it is recommended that parents monitor their children’s diets by providing a balanced, varied selection of nutritious foods that support the growth and development of preschool-age children.